Evaluation of Hookworm Diagnosis Techniques from Patients in Debre Elias and Sanja Districts of the Amhara Region, Ethiopia - Zeleke, Ayalew Jejaw; Addisu, Ayenew; Derso, Adane; Tegegne, Yalewayker; Birhanie, Meseret; Sisay, Tekeba; Aemero, Mulugeta (Journal of parasitology research, 2021)
Background. Inappropriate diagnosis could intimidate the prevention and control of hookworm infection. Thus, this study was aimed at evaluating the performance of hookworm diagnosis methods. Methods. An institution-based cross-sectional study was conducted from patients in Debre Elias and Sanja districts of the Amhara region, Ethiopia, from November 2019 to January 2020. The study subjects were selected conveniently. After the data was entered into Statistical Package for the Social Sciences (SPSS), sensitivity, specificity, predictive values, test accuracy, and agreement of the different hookworm diagnosis methods, namely, test tube flotation technique (TFT), McMaster (MM), formol-ether concentration (FEC), Kato-Katz (KK), and direct wet mount microscopy (DWMM), were calculated by using SPSS software. The composite reference standard (CRS) was used as the gold standard method. The kappa (κ) test was used to measure the level of agreement between diagnosis tests. Result. A total of 389 stool samples were collected from patients in the study. The overall prevalence of hookworm was 63.24%. The test tube flotation technique (TFT) was found to be the highest both in terms of sensitivity and diagnostic accuracy (100%). McMaster (MM) was the second most sensitive test (68.7%), followed by FEC (44.3%) and KK (38.2%). On the other hand, DWMM had the lowest sensitivity (37.4%), and its diagnostic accuracy was also the least (60%). Only TFT had a perfect agreement (agreement=100%, kappa=1) with the CRS. The sensitivity of DWMM, KK, and FEC showed a kind of linear function with the intensity of infection, but TFT and MM methods were not affected by the infection intensity. Conclusion. Hookworm is still a public health problem in the study area. TFT is by far more sensitive than MM, FEC, KK, and DWMM techniques.